Earlier voyages and future destinations in the study of tourism - Rice, Mark (2019)
This essay serves as the introduction to the issue of  Apuntes  dedicated to tourism. It defines the activity, provides a short history of its development, and revisits academic debates about the significance and consequences of tourism. Additionally, the essay reviews of the achievements in the study of tourism in Latin America and Peru in particular, suggests possible future avenues of research, and describes the contributions of the articles included in this issue of Apuntes.